The Effect of Cognitive Behavior Therapy (CBT) Approach Through Group Guidance Services to Increase Student Responsibility SMP Negeri 4 Kejuruan Muda - Annisa Syahfira; Alfin Siregar (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This study aims to explore the effect of the Cognitive Behavior Therapy (CBT) approach implemented through group guidance services on increasing student responsibility at SMP Negeri 4 Kejuruan Muda. Responsibility is a crucial aspect in students' academic and social development, but it is often a challenge that needs to be addressed effectively. The CBT approach, which focuses on changing mindsets and behaviors, is expected to help students develop better attitudes of responsibility. The type of research used is quasi-experimental. The number of samples used was 16 students included in the experimental and control groups. The population was 60 students. Data were collected through a student responsibility questionnaire. The results of the analysis showed that there was a significant increase in the level of responsibility of students who participated in CBT guidance compared to the control group. These findings indicate that the CBT approach through group guidance services can be an effective strategy to increase student responsibility in the school environment.